2020
DOI: 10.1002/pon.5507
|View full text |Cite
|
Sign up to set email alerts
|

Assessing competencies of healthcare professionals caring for parents with cancer: The development of an innovative assessment tool

Abstract: Objective: This paper describes the development of an assessment tool capturing competencies of healthcare professionals (HCPs) in caring for cancer patients with minor children. Methods: We combined the methods of clinical case vignettes and situational judgement tests (SJTs). Scenarios were created based on literature and interviews with patients, HCPs, and experts. We pretested the instrument by conducting cognitive interviews with n = 6 HCPs, who gave feedback on realism, clarity, and difficulty of the sce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Hence, there is a need for rigorously developed and psychometrically sound instruments. Moreover, objective simulated patient assessments (SPAs) should be included in future studies as they are the gold standard for evaluation of CSTs [ 51 , 52 ]. Clinical case vignettes, as used in one included study [ 23 ], have been found to be comparable to SPAs [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there is a need for rigorously developed and psychometrically sound instruments. Moreover, objective simulated patient assessments (SPAs) should be included in future studies as they are the gold standard for evaluation of CSTs [ 51 , 52 ]. Clinical case vignettes, as used in one included study [ 23 ], have been found to be comparable to SPAs [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary outcome was the competency to approach child‐ and family‐related themes in cancer patients. We developed a specific assessment tool, combining clinical case vignettes and situational judgment test methodology 24 . Each questionnaire included two clinical scenarios, reflecting cases of parents with cancer and measuring four domains: (1) transfer of knowledge into clinical practice, (2) empathic behavior toward affected parents, (3) integration of child‐ and family‐related themes into clinical practice ( behavior ) and (4) perceived relevance of integration.…”
Section: Methodsmentioning
confidence: 99%
“…Hu et al 20 emphasized that the purpose of spiritual care is to ease patients’ difficulties at the spiritual level and help them find meaning. Compared with other patients, the palliative care patients have more specific support and spiritual needs 21 . Hospice palliative care teams who witness the suffering and pain of patients in the face of an incurable disease may be more vulnerable to CF 22 …”
mentioning
confidence: 99%
“…Compared with other patients, the palliative care patients have more specific support and spiritual needs. 21 Hospice palliative care teams who witness the suffering and pain of patients in the face of an incurable disease may be more vulnerable to CF. 22 Although Fillion et al 14 conducted a meaning-centered education program based on Viktor Frankl's logotherapy 7 for palliative care nurses, to the best of our knowledge, there have been no studies involving HPCTs.…”
mentioning
confidence: 99%